Meat, beyond the plate: data-driven hypotheses for understanding consumer willingness to adopt a more plant-based diet - Graça, J.; Oliveira, A.; Calheiros, M. M. (Appetite, 2015)
A shift towards reduced meat consumption and a more plant-based diet is endorsed to promote sustainability, improve public health, and minimize animal suffering. However, large segments of consumers do not seem willing to make such transition. While it may take a profound societal change to achieve significant progresses on this regard, there have been limited attempts to understand the psychosocial processes that may hinder or facilitate this shift. This study provides an in-depth exploration of how consumer representations of meat, the impact of meat, and rationales for changing or not habits relate with willingness to adopt a more plant-based diet. Multiple Correspondence Analysis was employed to examine participant responses (N = 410) to a set of open-ended questions, free word association tasks and closed questions. Three clusters with two hallmarks each were identified: (1) a pattern of disgust towards meat coupled with moral internalization; (2) a pattern of low affective connection towards meat and willingness to change habits; and (3) a pattern of attachment to meat and unwillingness to change habits. The findings raise two main propositions. The first is that an affective connection towards meat relates to the perception of the impacts of meat and to willingness to change consumption habits. The second proposition is that a set of rationales resembling moral disengagement mechanisms (e.g., pro-meat justifications; self-exonerations) arise when some consumers contemplate the consequences of meat production and consumption, and the possibility of changing habits.